Les cowboys [videorecording (DVD)] - Bidegain, Thomas; Damiens, François, 1973-; Oldfield, Finnegan, 1991-; Dronne, Agathe (Cohen Media Group, 2016)
"A country and western gathering is being held in a vast prairie in the east of France. Alain (François Damiens) is a central figure in this community. He's dancing with his daughter as his wife and their young son Kid (Finnegan Oldfield) watch from the sidelines. But on this day, Alain's daughter disappears--and the family falls apart. Alain and Kid embark on a relentless search for her, even though it costs them everything and takes them to far-off and unsettling places"--Container.